Antibiotic following tonsillectomy: are we justified? - Mishra, Prasun; Patni, Digant; Kaushik, Maitri; Dehadaray, Arun (International Surgery Journal, 2016)
Background: Tonsillectomy remains one of the most commonly performed surgeries in ENT practice. Though rare, post-tonsillectomy hemorrhage is one of the most dreaded complications. Antibiotics are commonly used to reduce the risk of this complication. Not sufficient data is available to prove the use of antibiotics. Aim of current study was to study the role of antibiotics in prevention of post tonsillectomy secondary hemorrhage. Methods:Randomized control trial was done. Pilot study on 92 patients, operated for tonsillectomy was randomly divided in two groups. All patients were operated by dissection method and both groups were matched in terms of types of anesthesia and post op analgesia. The first group was given antibiotics following tonsillectomy and the other group was not given antibiotics. These patients were followed up for 14 days. Results:Only one patient in the group where antibiotic was given developed secondary hemorrhage and none of the patients in the non-antibiotic group developed any secondary hemorrhage. Conclusion: This study does provide a level I evidence suggesting that routine use of antibiotic is not justified following tonsillectomy however a study with larger data is advocated.